Brazilian Hydrography: The challenges of renewing Its Research Vessels - Palmer Fonseca (Brazil), Luiz Fernando (The International Hydrographic Review, 2015)
With the acquisition of new hydro-oceanographic vessels, the Directorate of Hydrography and Navigation (DHN) - Brazilian Hydrographic Service continues to meet its surveying and charting responsibilities within an extensive maritime and inland water domain. Amongst tight budgetary restrictions, the acquisition process for the new vessels required an updated, improved and optimized operational capability from that of the current capabilities of the existing research ships. For the acquisition process to progress, it was necessary to collaborate with the various private and government stakeholder organizations interested in the research results from surveys undertaken by these ships. This approach provided an overall capability that benefits the neighboring countries of the hydrographic basins of the Amazon and the Pantanal and those nations that share the borders in South Atlantic. This article describes the acquisition process undertaken by the Brazilian Hydrographic Service to renew the hydro-oceanographic vessels to ensure it can meet the responsibilities for at least the first quarter of the 21st Century.